Public Awareness about Disposal of Solid Waste and its Impact: A Study in Tangail Pourashava, Tangail (Journal of Environmental Science and Natural Resources, 2013)
The investigation was conducted on public awareness about disposal of solid waste and its impact in Thanapara, Beparipara and Kagmari of Tangail Pourashava. Data collected through questionnaire interview from local residents, self-observation and secondary sources. The investigation was conducted among three major infected areas by selecting normal dustbin and open area during the different period from August to September 2011. In the study, total 100 respondents are interviewed and the result shows that waste are dumped here three times a day. Most of the respondents demand for wrong site selection and improper maintenance causing bad odor, diarrheea, skin diseases, aesthetic problem etc. It was also found that the main sources of waste materials generation were the urban dwellers and most of the waste is dumped by metropolis. Some local people also dump their waste in the area. The study shows that the service holders, student respondents have better idea about the effects of dumping solid wastes at open sights than the other respondents.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14821 J. Environ. Sci. & Natural Resources, 5(2): 239-244 2012